C4 2017 2 Edexcel

2

Write:

\displaystyle f(x) = 2^{-3}\left(1 + \dfrac k 2\right)^{-3} = \frac 1 8 \left(1 + \dfrac k 2 x\right)^{-3}

(a)

We have \displaystyle A = \frac 1 8.

(b)

The coefficient of the x^2 term in the series expansion of \displaystyle \frac 1 8 \left(1 + \dfrac k 2 x\right)^{-3} is:

\displaystyle \frac 1 8 \times \frac {-3(-4)} 2 \left(\frac k 2\right)^2 = \frac 3 {16} k^2

and we have:

\displaystyle \frac 3 {16} k^2 = 243

So:

k^2 = 81

giving:

k = \pm 9

Since k is positive, we have k = 9.

©

The coefficient of the x term in the series expansion of (2 + 9x)^{-3} is:

\displaystyle B = \frac 1 8 \times (-3) \times \left(\frac 9 2\right) = -\dfrac {27} {16}

1 Like

:surfing_man: :surfing_man: :surfing_man: